The occurrence of wheat crown rot correlates with the microbial community and function in rhizosphere soil - Yajiao Wang; Jian Feng; Jianhai Gao; Sen Han; Qiusheng Li; Lingxiao Kong; Yuxing Wu (Frontiers in Microbiology)
Wheat crown rot (WCR) is a significant soil-borne disease affecting wheat production worldwide. Understanding the impact of wheat crown rot on the structure and function of microbial communities in the wheat rhizosphere soil can provide a theoretical basis for the mining biological control resources against WCR. In this study, rhizosphere soils with varying WCR severities (light, moderate, severe) were analyzed for chemical properties, microbial community composition and functions using high-throughput sequencing. The results revealed that WCR decreased rhizosphere soil pH, the content of available nitrogen and phosphorus, and the abundance of beneficial taxa such as Bacillus and Streptomyces. Additionally, functional predictions showed that microbial communities adapted to WCR by enhancing signaling pathways and reducing their anabolic activity. From soil with light WCR occurrence, we isolated Bacillus velezensis BF-237, whose abundance was reduced by WCR. Greenhouse experiments demonstrated that BF-237 achieved a control efficiency of 56.61% against WCR in artificially inoculated sterilized soil and 53.32% in natural soil. This study clarifies the impact of wheat crown rot on the community structure, and function of rhizosphere soil microorganisms, alongside identifying a promising biocontrol agent. These findings contribute to understanding WCR pathogenesis and offer practical resources for its management.